2022
DOI: 10.1002/jbt.23067
|View full text |Cite
|
Sign up to set email alerts
|

A review of the mutagenic potential of N‐ethyl‐N‐nitrosourea (ENU) to induce hematological malignancies

Abstract: This review is intended to summarize the existing literature on the mutagenicity of N-ethyl-N-nitrosourea (ENU) in inducing hematological malignancies, including acute myeloid leukemia (AML) in mice. Blood or hematological malignancies are the most common malignant disorders seen in people of all age groups. Driven by a number of genetic alterations, leukemia rule out the normal proliferation and differentiation of hematopoietic stem cells (HSCs) and their progenitors in the bone marrow (BM) and severely affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 126 publications
(227 reference statements)
0
4
0
Order By: Relevance
“…The structures of the target compounds 8a-j were confirmed by spectral data, including different spectroscopic techniques. 1 H NMR spectra showed the characteristics of two ═C-H protons at δ 7.05-7.64 ppm attributed to styryl moiety with J = 15.4-16.0 Hz, which confirms the trans geometry of styryl moiety at position 2 and chalcone protons at δ 7.79-8.09 ppm with J = 15.2-15.7 Hz, which also indicates trans geometry. Increasing the integration of aromatic protons attributed to the additional phenyl rings was recognized and appeared in the 1 H NMR spectra.…”
Section: Chemistrymentioning
confidence: 66%
See 1 more Smart Citation
“…The structures of the target compounds 8a-j were confirmed by spectral data, including different spectroscopic techniques. 1 H NMR spectra showed the characteristics of two ═C-H protons at δ 7.05-7.64 ppm attributed to styryl moiety with J = 15.4-16.0 Hz, which confirms the trans geometry of styryl moiety at position 2 and chalcone protons at δ 7.79-8.09 ppm with J = 15.2-15.7 Hz, which also indicates trans geometry. Increasing the integration of aromatic protons attributed to the additional phenyl rings was recognized and appeared in the 1 H NMR spectra.…”
Section: Chemistrymentioning
confidence: 66%
“…The Shimadzu fourier-transform infrared (FT-IR) spectrometer Affinity A1 was used to record IR spectra as films on KBr plates. The reaction's progress was monitored using thin-layer chromatography (Merck) and visualized by UV Lamp 254 nm 1. H NMR and13 C NMR spectra were measured on a Bruker Avance III 400 MHz for 1 H NMR and 100 MHz for13 C NMR (Bruker AG) with BBFO Smart Probe and Bruker 400 AEON Nitrogen-Free Magnet, Faculty of Pharmacy, Beni-Suef University, Egypt, in DMSO-d 6 with tetramethyl silane as the internal standard, where J (coupling constant) values are estimated in Hertz (Hz) and chemical shifts were recorded in ppm on δ scale and signals expressed as s, d, t, and m. Elemental analyses were recorded on Shimadzu GC/ MS-QP5050A, Regional Center for Mycology and Biotechnology, Al-Azhar University, Cairo, Egypt.…”
mentioning
confidence: 99%
“…Therefore, ROS formation can play an integral role in carcinogenesis and the development of various cancers after exposure with chemical carcinogens [35] . It is well established that alkylating agents such as ENU contribute to carcinogenesis and toxicity via induction of oxidative stress due to increase in reactive oxygen and nitrogen species, glutathione depletion and lipid peroxidation [6] , [36] . Our results consistent with these studies showed that ENU as a full carcinogen agent induces ROS formation, MDA production and oxidative stress in lymphocytes as target cells in CLL.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Specifically, nitrosoureas like n-ethyl-n-nitrosourea (ENU) have been found to induce leukemia by alkylating nucleobases, disrupting DNA, and resulting in bone marrow suppression and the formation of leukemic cells. 30 , 31 ENU has also been observed to generate malignant cells in the brain and reproductive system in animal models. 4 , 32 Any disruption in the signaling cascade that regulates differentiation and proliferation can lead to hematological abnormalities, resulting in a buildup of cancerous cells in the bone marrow and blood.…”
Section: Discussionmentioning
confidence: 99%